Air pollution, aeroallergens and admissions to pediatric emergency room for respiratory reasons in Turin, northwestern Italy. (December 2016) - Bono, Roberto; Romanazzi, Valeria; Bellisario, Valeria; Tassinari, Roberta; Trucco, Giulia; Urbino, Antonio; Cassardo, Claudio; Siniscalco, Consolata; Marchetti, Pierpaolo; Marcon, Alessandro
Abstract Background Air pollution can cause respiratory symptoms or exacerbate pre-existing respiratory diseases, especially in children. This study looked at the short-term association of air pollution concentrations with Emergency Room (ER) admissions for respiratory reasons in pediatric age (0–18 years). Methods Daily number of ER admissions in a children's Hospital, concentrations of urban-background PM2.5, NO2, O3 and total aeroallergens (Corylaceae, Cupressaceae, Gramineae, Urticaceae, Ambrosia, Betula) were collected in Turin, northwestern Italy, for the period 1/08/2008 to 31/12/2010 (883 days). The associations between exposures and ER admissions were estimated, at time lags between 0 and 5 days, using generalized linear Poisson regression models, adjusted for non-meteorological potential confounders. Results In the study period, 21, 793 ER admissions were observed, mainly (81 %) for upper respiratory tract infections. Median air pollution concentrations were 22.0, 42.5, 34.1 μg/m3 for urban-background PM2.5, NO2, and O3, respectively, and 2.9 grains/m3 for aeroallergens. We found that ER admissions increased by 1.3 % (95 % CI: 0.3-2.2 %) five days after a 10 μg/m3 increase in NO2, and by 0.7 % (95 % CI: 0.1-1.2 %) one day after a 10 grains/m3 increase in aeroallergens, while they were not associated with PM2.5 concentrations. ER admissions were negatively associated with O3 and aeroallergen concentrations at some time lags, but these association shifted to the null when meteorological confounders were adjusted for in the models. Conclusions Overall, these findings confirm adverse short-term health effects of air pollution on the risk of ER admission in children and encourage a careful management of the urban environment to health protection.